2019
DOI: 10.1093/alcalc/agz030
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Human Metabolome Associated With Alcohol Use: A Review

Abstract: Aims: The metabolome refers to the functional status of the cell, organ, or the whole body. Metabolomic methods measure the metabolome (metabolite profile) which can be used to examine disease progression and treatment responses. Here, our aim was to review metabolomics studies examining effects of alcohol use in humans. Methods: We performed a literature search using PubMed and Web of Science for reports on changes in the human metabolite profile associated with alcohol use; we found a total of 23 articles pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 51 publications
7
24
0
Order By: Relevance
“…In the present study, high self-reported alcohol use was associated with alterations in different amino acids, glycerophospholipids, steroid hormones, pyrimidines, and fatty acids (Table 2). These results are in line with previous studies showing that alcohol use alters the circulating metabolome in these compound classes (Heikkinen et al, 2019;Jaremek et al, 2013;Lacruz et al, 2016;Lehikoinen et al, 2018;Pallister et al, 2016;van Roekel et al, 2018;Voutilainen and K€ arkk€ ainen, 2019;W€ urtz et al, 2016;Zheng et al, 2014); it is also known that the levels of compounds in these classes are altered in organs like brain and liver in association with alcohol use disorder (K€ arkk€ ainen et al, 2016;Kashem et al, 2016;Schofield et al, 2017). Moreover, alterations in metabolites associated with gut microbiota, like 3-indolepropionic acid and hippuric acid, were evident between the study groups.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, high self-reported alcohol use was associated with alterations in different amino acids, glycerophospholipids, steroid hormones, pyrimidines, and fatty acids (Table 2). These results are in line with previous studies showing that alcohol use alters the circulating metabolome in these compound classes (Heikkinen et al, 2019;Jaremek et al, 2013;Lacruz et al, 2016;Lehikoinen et al, 2018;Pallister et al, 2016;van Roekel et al, 2018;Voutilainen and K€ arkk€ ainen, 2019;W€ urtz et al, 2016;Zheng et al, 2014); it is also known that the levels of compounds in these classes are altered in organs like brain and liver in association with alcohol use disorder (K€ arkk€ ainen et al, 2016;Kashem et al, 2016;Schofield et al, 2017). Moreover, alterations in metabolites associated with gut microbiota, like 3-indolepropionic acid and hippuric acid, were evident between the study groups.…”
Section: Discussionsupporting
confidence: 93%
“…For example, high glutamate levels at the baseline seem to predict favorable responses to acamprosate treatment (Hinton et al, 2017;Nam et al, 2015). However, most of the studies so far have been cross-sectional or case-control studies, where persons with heavy alcohol use history are compared to light drinking controls, where it is impossible to say which of the changes in the metabolome precede the diagnosis of alcoholrelated disease (Voutilainen and K€ arkk€ ainen, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In view of the morbidity and mortality of ACM, many studies have explored the pathogenesis of ACM in recent years. Although previous studies have reported metabolomics profiles after alcohol consumption, most studies have chosen serum or plasma as the research object [7]. However, systematic factors in a living organism may affect blood circulation, and the observed metabolic changes in circulating serum or plasma may not only be due to the myocardial injury induced by chronic alcohol consumption [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…The metabolome can be divided into three categories: All endogenous metabolites in living organisms, microbial metabolites produced by microorganisms, and all foreign metabolites derived from xenobiotics [1]. Metabolomics, a holistic analytical approach to studying metabolomes, is a powerful tool in understanding the comprehensive changes in metabolic responses in living systems induced by external stimuli or genetic alterations and is the endpoint of the omics cascade [2,3,4,5]. Unlike genomics, transcriptomics, and proteomics, metabolomics reflects the phenotype of living things, enabling us to observe simultaneous changes in many metabolites, thus aiding the discovery of biomarkers for disease diagnosis and facilitating the determination of the metabolic effects on toxicity and the exploration of the action mechanisms in pathogenesis [6,7,8,9,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%